Copolymer composition for conveyor belt and use thereof

The copolymer composition for conveyor belts, featuring ethylene/α-olefin/nonconjugated polyene copolymer and additives, addresses the challenge of high abrasion and heat resistance, resulting in a conveyor belt with enhanced durability and longevity.

JP7613972B2Active Publication Date: 2025-01-15MITSUI CHEMICALS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021048694
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-23
Publication Date
2025-01-15
Estimated Expiration
2041-03-23

AI Technical Summary

Technical Problem

Conveyor belts used for transporting high-temperature goods face challenges in achieving high abrasion resistance while maintaining mechanical properties and heat aging resistance, as existing rubber compositions do not meet the increasing demand for improved performance.

Method used

A copolymer composition for conveyor belts comprising ethylene/α-olefin/nonconjugated polyene copolymer, carbon black, and an anti-aging agent, with specific molar ratios and molecular weight characteristics, to enhance wear resistance, mechanical properties, and heat aging resistance.

Benefits of technology

The copolymer composition provides a heat-resistant conveyor belt with improved abrasion resistance, mechanical properties, and heat aging resistance, ensuring extended service life and reduced maintenance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613972000001
    Figure 0007613972000001
  • Figure 0007613972000002
    Figure 0007613972000002
  • Figure 0007613972000003
    Figure 0007613972000003
Patent Text Reader

Abstract

To provide a copolymer composition for conveyor belts that is suitable for obtaining a conveyor belt having excellent processability, mechanical properties, thermal-aging resistance and wear resistance.SOLUTION: A copolymer composition for conveyor belts comprises an ethylene-α-olefin-nonconjugated polyene copolymer (S), an ethylene-α-olefin copolymer (F), carbon black (G) and an age resister (H).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copolymer composition for use in a conveyor belt, which has excellent processability, mechanical properties, heat aging resistance and abrasion resistance. [Background technology]

[0002] In various industrial fields such as steel, coal, and cement, belt conveyor devices are used as a means of transporting goods, and in particular, there are many cases where high-temperature goods such as clinker, which are about 150 to 250°C, are transported by belt conveyor devices. In view of this situation, there is a demand for conveyor belts with excellent heat aging resistance and wear resistance in order to minimize maintenance work and extend the service life.

[0003] As a method for improving the heat aging resistance, abrasion resistance, etc. of conveyor belts, it has been proposed to use a rubber composition containing an ethylene-1-octene copolymer and an ethylene-propylene copolymer (Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-246017 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in recent years, there has been an increasing demand for higher abrasion resistance in conveyor belts, and it is desired that rubber compositions for heat-resistant conveyor belts that replace conventional products maintain or exceed the heat resistance, mechanical properties, and processability of conventional products.

[0006] An object of the present invention is to obtain a copolymer composition for a conveyor belt which is suitable for producing a conveyor belt having excellent processability, mechanical properties, heat aging resistance and abrasion resistance. [Means for solving the problem]

[0007] As a result of investigations aimed at solving the above problems, the present inventors have found that the above problems can be solved by a composition having the following configuration, and have thus completed the present invention. The present invention relates to a copolymer composition for use in a conveyor belt, comprising the following components (S), (F), (G) and (H): (S) An ethylene-α-olefin-non-conjugated polyene copolymer having structural units derived from ethylene (A), an α-olefin (B) having 3 to 20 carbon atoms, and a non-conjugated polyene (C) containing in the molecule two or more partial structures in total selected from the group consisting of the following general formulas (I) and (II), and satisfying the following requirements (i) to (v): (F) an ethylene-α-olefin copolymer containing ethylene and an α-olefin having 3 to 20 carbon atoms; (G) carbon black; (H) anti-aging agents; Ethylene-α-olefin-non-conjugated polyene copolymer (S); [ka] (i) The molar ratio of ethylene / α-olefin is 40 / 60 to 99.9 / 0.1. (ii) The weight fraction of the constitutional units derived from the non-conjugated polyene (C) is 0.07% by weight to 10% by weight in 100% by weight of the ethylene-α-olefin-non-conjugated polyene copolymer. (iii) The weight average molecular weight (Mw) of the ethylene-α-olefin-non-conjugated polyene copolymer, the weight fraction of the constitutional unit derived from the non-conjugated polyene (C) (weight fraction (wt%) of (C)), and the molecular weight of the non-conjugated polyene (C) (molecular weight of (C)) satisfy the following formula (1). 4.5≦Mw×weight fraction of (C) / 100 / molecular weight of (C)≦40 Equation (1) (iv) Complex viscosity η at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurement (190 °C) using a rheometer * ( ω =0.1)(Pa sec) and the complex viscosity η at frequency ω = 100 rad / s * ( ω =100) (Pa sec) * ( ω =0.1) / η * ( ω =100) ), the intrinsic viscosity [η], and the weight fraction of the constitutional unit derived from the non-conjugated polyene (C) (weight fraction of (C)) satisfy the following formula (2). P / ([η] 2.9 ) ≦ Weight fraction of (C) × 6 Equation (2) (v) Number of long chain branches (LCB) per 1000 carbon atoms obtained using 3D-GPC 1000C ) and the natural logarithm of the weight average molecular weight (Mw) [Ln(Mw)] satisfy the following formula (3). LCB 1000C ≦1-0.07×Ln(Mw)···Equation (3) Effect of the Invention

[0008] The rubber composition for a heat-resistant conveyor belt of the present invention can provide a heat-resistant conveyor belt having high abrasion resistance while maintaining processability, mechanical properties, and heat aging resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <Ethylene / α-olefin / non-conjugated polyene copolymer (S)> The ethylene-α-olefin-non-conjugated polyene copolymer (S), which is one of the components contained in the copolymer composition for a conveyor belt of the present invention (hereinafter sometimes abbreviated as "component (S)"), has constitutional units derived from ethylene (A), an α-olefin (B) having 3 to 20 carbon atoms, and a non-conjugated polyene (C) containing in the molecule a total of two or more partial structures selected from the group consisting of the following general formulae (I) and (II):

[0010] [ka]

[0011] The component (S) according to the present invention may further have a structural unit derived from a non-conjugated polyene (D) containing in the molecule only one partial structure selected from the group consisting of the general formulae (I) and (II) in addition to the structural units derived from the above (A), (B), and (C).

[0012] Examples of the α-olefin (B) having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-eicosene. Among these, α-olefins having 3 to 8 carbon atoms such as propylene, 1-butene, 1-hexene, and 1-octene are preferred, and propylene is particularly preferred. Such α-olefins are preferred because the raw material cost is relatively low, the resulting copolymer composition for conveyor belts exhibits excellent mechanical properties, and a conveyor belt having rubber elasticity can be obtained. These α-olefins may be used alone or in combination.

[0013] Component (S) according to the present invention contains structural units derived from at least one type of α-olefin (B) having 3 to 20 carbon atoms, and may contain structural units derived from two or more types of α-olefins (B) having 3 to 20 carbon atoms.

[0014] Examples of the non-conjugated polyene (C) containing two or more partial structures selected from the group consisting of the general formulae (I) and (II) in the molecule in total include 5-vinyl-2-norbornene (VNB), norbornadiene, 1,4-hexadiene, and dicyclopentadiene. Among these, it is preferable that the non-conjugated polyene (C) contains VNB, and it is more preferable that the non-conjugated polyene (C) is VNB, because it is highly available, has good reactivity with peroxide during crosslinking reaction after polymerization, and is likely to improve the heat resistance of the copolymer composition for conveyor belts. The non-conjugated polyene (C) may be used alone or in combination of two or more kinds.

[0015] The component (S) according to the present invention may contain, in addition to the structural units derived from ethylene (A), the α-olefin (B) having 3 to 20 carbon atoms, and the non-conjugated polyene (C), a structural unit derived from a non-conjugated polyene (D) containing in the molecule only one partial structure selected from the group consisting of the general formulae (I) and (II). Examples of such non-conjugated polyenes (D) include 5-ethylidene-2-norbornene (ENB), 5-methylene-2-norbornene, 5-(2-propenyl)-2-norbornene, 5-(3-butenyl)-2-norbornene, 5-(1-methyl-2-propenyl)-2-norbornene, 5-(4-pentenyl)-2-norbornene, 5-(1-methyl-3-butenyl)-2-norbornene, 5-(5-hexenyl)-2-norbornene, 5-(1-methyl-4-pentenyl)-2-norbornene, 5-(2,3-dimethyl-3-butenyl)-2-norbornene, 5-(2-ethyl-3-butenyl)-2-norbornene, 5-(6-heptenyl)-2-norbornene, 5-(3-methyl-5-hexenyl)-2-norbornene, 5-(3,4-dimethyl-4-pentenyl)-2-norbornene, 5-(3-ethyl-4-pentenyl)-2-norbornene, 5-(7-octenyl)-2-norbornene, 5-(2-methyl-6-heptenyl)-2-norbornene, 5-(1,2-dimethyl-5-hexenyl)-2-norbornene, 5-(5-ethyl-5-hexenyl)-2-norbornene, 5-(1,2,3-trimethyl-4-pentenyl)-2-norbornene, and the like. Among these, ENB is preferred because it is easily available, has high reactivity with sulfur and vulcanization accelerators during the crosslinking reaction after polymerization, is easy to control the crosslinking rate, and is easy to obtain good mechanical properties. The non-conjugated polyene (D) may be used alone or in combination of two or more kinds.

[0016] When the ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention contains a structural unit derived from a non-conjugated polyene (D) containing only one partial structure selected from the group consisting of the general formulae (I) and (II) in the molecule, the proportion of the structural unit is not particularly limited as long as it does not impair the object of the present invention, but is usually contained in a weight fraction of about 0 to 20% by weight, preferably 0 to 8% by weight, and more preferably 0.01 to 8% by weight (wherein the total weight fractions of (A), (B), (C) and (D) is taken as 100% by weight).

[0017] As described above, the component (S) according to the present invention is a copolymer having structural units derived from ethylene (A), an α-olefin (B) having 3 to 20 carbon atoms, the non-conjugated polyene (C), and, if necessary, the non-conjugated polyene (D), and satisfies the following requirements (i) to (v).

[0018] [Requirement (i)] The molar ratio of ethylene / α-olefin is 40 / 60 to 99.9 / 0.1.

[0019] [Requirement (ii)] The weight fraction of the constitutional units derived from the non-conjugated polyene (C) is 0.07% by weight to 10% by weight.

[0020] [Requirement (iii)] The weight average molecular weight (Mw) of the ethylene-α-olefin-non-conjugated polyene copolymer (S), the weight fraction of the constitutional unit derived from the non-conjugated polyene (C) (weight fraction (wt%) of (C)), and the molecular weight of the non-conjugated polyene (C) (molecular weight of (C)) satisfy the following formula (1). 4.5≦Mw×weight fraction of (C) / 100 / molecular weight of (C)≦40 Equation (1)

[0021] [Requirement (iv)] Complex viscosity η at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurements (190 °C) using a rheometer * ( ω =0.1) (Pa sec) and the complex viscosity η at frequency ω = 100 rad / s* ( ω =100) (Pa sec) * ( ω =0.1) / η * ( ω =100) ), the intrinsic viscosity [η], and the weight fraction of the constitutional unit derived from the non-conjugated polyene (C) (weight fraction of (C)) satisfy the following formula (2). P / ([η] 2.9 ) ≦ Weight fraction of (C) × 6 Equation (2)

[0022] [Requirement (v)] The number of long chain branches (LCB) per 1000 carbon atoms obtained using 3D-GPC 1000C ) and the natural logarithm of the weight average molecular weight (Mw) [Ln(Mw)] satisfy the following formula (3). LCB 1000C ≦1-0.07×Ln(Mw)···Equation (3) In this specification, "α-olefin having 3 to 20 carbon atoms" may also be simply referred to as "α-olefin".

[0023] [Requirement (i)] Requirement (i) specifies that the molar ratio of ethylene / α-olefin in the ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention satisfies 40 / 60 to 99.9 / 0.1, and this molar ratio preferably satisfies 50 / 50 to 90 / 10, more preferably 55 / 45 to 85 / 15, and further preferably 55 / 45 to 78 / 22. When such an ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention is used as a raw material for a crosslinked molded article, the resulting crosslinked molded article exhibits excellent rubber elasticity and is excellent in mechanical strength and flexibility, which is preferable.

[0024] The ethylene content (content of constituent units derived from ethylene (A)) and the α-olefin content (content of constituent units derived from α-olefin (B)) in the ethylene-α-olefin-non-conjugated polyene copolymer (S) are 13 It can be determined by C-NMR.

[0025] [Requirement (ii)] Requirement (ii) specifies that the weight fraction of the structural unit derived from the non-conjugated polyene (C) in the component (S) according to the present invention is in the range of 0.07% by weight to 10% by weight in 100% by weight of the ethylene-α-olefin-non-conjugated polyene copolymer (S) (i.e., in the total weight fraction of all structural units, 100% by weight). The weight fraction of the structural unit derived from the non-conjugated polyene (C) is preferably 0.1% by weight to 8.0% by weight, more preferably 0.5% by weight to 5.0% by weight.

[0026] When the component (S) according to the present invention satisfies the requirement (ii), the component (S) according to the present invention has sufficient hardness and excellent mechanical properties, which is preferable, and when crosslinked using a peroxide, it shows a fast crosslinking rate, and the component (S) according to the present invention is preferable because it is suitable for producing a crosslinked molded article. The amount of non-conjugated polyene (C) in the ethylene-α-olefin-non-conjugated polyene copolymer (S) (the content of constituent units derived from non-conjugated polyene (C)) is 13 It can be determined by C-NMR.

[0027] [Requirement (iii)] Requirement (iii) specifies that, in the ethylene-α-olefin-non-conjugated polyene copolymer (S) of the present invention, the weight average molecular weight (Mw) of the ethylene-α-olefin-non-conjugated polyene copolymer, the weight fraction of the constituent unit derived from the non-conjugated polyene (C) in the copolymer (weight fraction of (C): weight %), and the molecular weight of the non-conjugated polyene (C) (molecular weight of (C)) satisfy the following relationship (1). 4.5≦Mw×weight fraction of (C) / 100 / molecular weight of (C)≦40 Equation (1)

[0028] When the ethylene-α-olefin-non-conjugated polyene copolymer (S) of the present invention satisfies the requirement (iii), the content of structural units derived from the non-conjugated polyene (C) such as VNB is appropriate, and sufficient crosslinking performance is exhibited. In addition, when a crosslinked molded article is produced using the ethylene-α-olefin-non-conjugated polyene copolymer of the present invention, the crosslinking rate is excellent and the molded article after crosslinking exhibits excellent mechanical properties, which is preferable.

[0029] It is more desirable that the ethylene / α-olefin / non-conjugated polyene copolymer (S) according to the present invention satisfies the following relational formula (1′): 4.5≦Mw×weight fraction of (C) / 100 / molecular weight of (C)≦35...Equation (1') The weight average molecular weight (Mw) of the ethylene-α-olefin-non-conjugated polyene copolymer (S) can be determined as a polystyrene-equivalent value measured by gel permeation chromatography (GPC).

[0030] The ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention has an appropriate degree of crosslinking when "Mw × weight fraction of (C) / 100 / molecular weight of (C)" satisfies the above formula (1) or (1'), and by using this, molded articles with excellent balance between mechanical properties and heat aging resistance can be produced. If "Mw × weight fraction of (C) / 100 / molecular weight of (C)" is too low, the crosslinking may be insufficient, resulting in a slow crosslinking rate, whereas if it is too high, excessive crosslinking may occur, resulting in deterioration of mechanical properties.

[0031] [Requirement (iv)] Requirement (iv) is that the complex viscosity η of the ethylene-α-olefin-non-conjugated polyene copolymer according to the present invention is measured by linear viscoelasticity at 190°C using a rheometer at a frequency of ω = 0.1 rad / s. * ( ω =0.1) (Pa sec) and the complex viscosity η at frequency ω = 100 rad / s * ( ω =100)(Pa sec) * ( ω =0.1) / η * ( ω =100) ), the intrinsic viscosity [η], and the weight fraction of the structural unit derived from the non-conjugated polyene (C) (weight fraction of (C): weight %) satisfy the following formula (2). P / ([η] 2.9 ) ≦ Weight fraction of (C) × 6 Equation (2)

[0032] Here, the complex viscosity η at frequency ω=0.1rad / s * ( ω =0.1) and the complex viscosity η at frequency ω=100rad / s * ( ω =100) Relative to P(η * ( ω =0.1) / η * ( ω =100) ) represents the frequency dependence of viscosity and is the left side of equation (2), P / ([η] 2.9 ) tends to show a high value when there are many long chain branches, although it is influenced by short chain branches and molecular weight. In general, the more structural units derived from non-conjugated polyenes contained in an ethylene-α-olefin-non-conjugated polyene copolymer, the more long chain branches there are. However, the ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention has fewer long chain branches than the conventionally known ethylene-α-olefin-non-conjugated polyene copolymers, and is therefore considered to be able to satisfy the above formula (2). In the present invention, the P value is determined by calculating the ratio (η* ratio) of the complex viscosity at 0.1 rad / s and the complex viscosity at 100 rad / s, which are measured using a viscoelasticity measuring device Ares (manufactured by Rheometric Scientific) under conditions of 190°C, strain 1.0%, and varying frequencies.

[0033] The ethylene / α-olefin / non-conjugated polyene copolymer (S) according to the present invention preferably satisfies the following formula (2'): P / ([η]2.9 ) ≦ Weight fraction of (C) × 5.7 Equation (2') The intrinsic viscosity [η] means a value measured in decalin at 135°C.

[0034] [Requirement (v)] Requirement (v) is the number of long chain branches (LCB) per 1,000 carbon atoms of the ethylene-α-olefin-non-conjugated polyene copolymer (S) obtained by 3D-GPC. 1000C ) and the natural logarithm of the weight average molecular weight (Mw) [Ln(Mw)] satisfy the following formula (3). LCB 1000C ≦1-0.07×Ln(Mw)···Equation (3)

[0035] The above formula (3) specifies the upper limit of the long chain branch content per unit carbon number of the ethylene-α-olefin-non-conjugated polyene copolymer (S).

[0036] Such an ethylene-α-olefin-non-conjugated polyene copolymer (S) is preferred because it contains a small proportion of long chain branches, has excellent curing properties when crosslinked using a peroxide, and provides molded articles having excellent heat aging resistance.

[0037] The ethylene / α-olefin / non-conjugated polyene copolymer (S) according to the present invention preferably satisfies the following formula (3'): LCB 1000C ≦1-0.071×Ln(Mw)...Equation (3') Here, Mw and the number of long chain branches (LCB) per 1000 carbon atoms 1000C ) can be determined by a structural analysis method using 3D-GPC. In this specification, it was specifically determined as follows.

[0038] The absolute molecular weight distribution was measured using a 3D-high temperature GPC device PL-GPC220 (Polymer Laboratories), and the intrinsic viscosity was measured using a viscometer. The main measurement conditions were as follows: Detector: Differential refractometer / GPC device built-in 2-angle light scattering photometer PD2040 type (manufactured by Precison Detectors) Bridge type viscometer PL-BV400 (Polymer Laboratories) Column: TSKgel GMH HR -H(S)HT x 2 + TSKgel GMH HR -M(S)×1 piece (Each piece has an inner diameter of 7.8 mm and a length of 300 mm) Temperature: 140℃ Mobile phase: 1,2,4-trichlorobenzene (containing 0.025% BHT) Injection volume: 0.5mL Sample concentration: ca 1.5mg / mL Sample filtration: Filtration through a sintered filter with a pore size of 1.0 μm The dn / dc value required to determine the absolute molecular weight was determined for each sample from the dn / dc value of standard polystyrene (molecular weight 190,000), 0.053, and the response intensity of the differential refractometer per unit injected mass.

[0039] The long chain branching parameter g'i for each eluted component was calculated from the relationship between the intrinsic viscosity obtained from the viscometer and the absolute molecular weight obtained from the light scattering photometer using formula (v-1).

[0040]

number

[0041] Here, [η] = KM v The relationship ;v=0.725 was applied. Further, the average values ​​of g' were calculated from the following formulas (v-2), (v-3), and (v-4). Note that a trendline assuming the presence of only short chain branches was determined for each sample.

[0042]

number

[0043] Furthermore, using g'w, the number of branch points per molecular chain, BrNo, and the number of long chain branches per 1000 carbon atoms, LCB, 1000C The branching degree λ per unit molecular weight was calculated. BrNo was calculated using the Zimm-Stockmayer formula (v-5). 1000C Equations (v-6) and (v-7) were used to calculate and λ. g is the long chain branching parameter calculated from the radius of gyration Rg, and the following simple correlation is made between g' calculated from the intrinsic viscosity. Various values ​​have been proposed for ε in the equation depending on the shape of the molecule. Here, calculations were performed assuming ε=1 (i.e. g'=g).

[0044]

number

[0045] The ethylene / α-olefin / non-conjugated polyene copolymer (S) according to the present invention preferably has an intrinsic viscosity [η] of 0.1 to 5 dL / g, more preferably 0.5 to 5.0 dL / g, and even more preferably 0.9 to 4.0 dL / g.

[0046] The ethylene / α-olefin / non-conjugated polyene copolymer (S) according to the present invention preferably has a weight average molecular weight (Mw) of 10,000 to 600,000, more preferably 30,000 to 500,000, and even more preferably 50,000 to 400,000.

[0047] The component (S) according to the present invention preferably satisfies both of the above-mentioned intrinsic viscosity [η] and weight average molecular weight (Mw). In the component (S) according to the present invention, the non-conjugated polyene (C) preferably contains VNB, and more preferably is VNB. That is, in the above-mentioned formula (1), formula (2) and formula (4) described later, it is preferable that the "weight fraction of (C)" is the "weight fraction of VNB" (% by weight).

[0048] As described above, in addition to the structural units derived from the above (A), (B) and (C), the component (S) according to the present invention also preferably contains a structural unit derived from a non-conjugated polyene (D) containing only one partial structure selected from the group consisting of the general formulas (I) and (II) in the molecule, in a weight fraction of 0 to 20% by weight (where the total weight fractions of (A), (B), (C) and (D) are taken as 100% by weight). In this case, it is preferable that the following requirement (vi) is satisfied.

[0049] [Requirement (vi)] The weight average molecular weight (Mw) of the ethylene-α-olefin-non-conjugated polyene copolymer, the weight fraction of the constituent unit derived from the non-conjugated polyene (C) (weight fraction (wt%) of (C)), the weight fraction of the constituent unit derived from the conjugated polyene (D) (weight fraction (wt%) of (D)), the molecular weight of the non-conjugated polyene (C) (molecular weight of (C)), and the molecular weight of the conjugated polyene (D) (molecular weight of (D)) satisfy the following formula (4). 4.5≦Mw×{(weight fraction of (C) / 100 / molecular weight of (C))+(weight fraction of (D) / 100 / molecular weight of (D))}≦45...Equation (4) Equation (4) specifies the content of non-conjugated diene (the sum of (C) and (D)) in one copolymer molecule.

[0050] When the ethylene-α-olefin-non-conjugated polyene copolymer containing the structural unit derived from (D) satisfies formula (4), a conveyor belt obtained from the ethylene-α-olefin-non-conjugated polyene copolymer preferably exhibits excellent mechanical properties and heat aging resistance.

[0051] If the requirement (vi) is not satisfied and "Mw × {(weight fraction of (C) / 100 / molecular weight of (C)) + (weight fraction of (D) / 100 / molecular weight of (D))}" in formula (4) is too small, that is, if the content of non-conjugated diene is too small, sufficient crosslinking may not be achieved and appropriate mechanical properties may not be obtained. Conversely, if the content is too high, excessive crosslinking may result in deterioration of mechanical properties and / or heat aging resistance.

[0052] [Requirement (vii)] The component (S) according to the present invention is not particularly limited, but it is preferably a compound having a complex viscosity η at a frequency ω=0.01 rad / s obtained by linear viscoelasticity measurement (190° C.) using a rheometer. * ( ω =0.01) (Pa sec) and the complex viscosity η at frequency ω=10rad / s * ( ω =10) It is preferable that the apparent iodine value (Pa·sec) and the apparent iodine value derived from the non-conjugated polyene (c) satisfy the following formula (5). Log{η * ( ω =0.01)} / Log{η * ( ω =10)}≦0.0753×{apparent iodine value derived from non-conjugated polyene (C)}+1.42···Equation (5) Here, the complex viscosity η * ( ω =0.01) and the complex viscosity η * ( ω =10) is the complex viscosity η in requirement (vi) * ( ω =0.1) and the complex viscosity η * ( ω =100) The same procedure is used to calculate the value of the frequency of the measurement.

[0053] The apparent iodine value derived from the non-conjugated polyene (C) is calculated by the following formula: Apparent iodine value derived from (C) = weight fraction of (C) × 253.81 / molecular weight of (C) In the above formula (5), the left side represents the shear rate dependency which is an index of the amount of long chain branches, and the right side represents an index of the content of non-conjugated polyene (C) that is not consumed as long chain branches during polymerization. When requirement (vii) and formula (5) are satisfied, the degree of long chain branching is not too high, which is preferable. On the other hand, when formula (5) is not satisfied, it is found that a large proportion of the copolymerized non-conjugated polyene (C) is consumed to form long chain branches.

[0054] Furthermore, the ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention preferably contains a sufficient amount of structural units derived from the non-conjugated polyene (C), and it is preferable that the weight fraction of the structural units derived from the non-conjugated polyene (C) in the copolymer (weight fraction (wt%) of (C)) and the weight average molecular weight (Mw) of the copolymer satisfy the following formula (6): 6-0.45×Ln(Mw)≦weight fraction of (C)≦10...Equation (6)

[0055] The ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention has a number of constitutional units (n C ) is preferably 6 or more, more preferably 6 to 40, even more preferably 7 to 39, and even more preferably 10 to 38.

[0056] The ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention contains a sufficient amount of structural units derived from a non-conjugated polyene (C) such as VNB, has a low content of long chain branches, is excellent in curing characteristics when crosslinked using a peroxide, has good moldability, and is excellent in balance of physical properties such as mechanical properties, as well as being particularly excellent in heat aging resistance.

[0057] Furthermore, the ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention has a number of constitutional units (n D) is preferably 29 or less, more preferably 10 or less, and even more preferably less than 1.

[0058] The ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention is preferable because the content of structural units derived from the non-conjugated polyene (D) such as ENB is controlled within a range that does not impair the object of the present invention, it is less likely to cause post-crosslinking, and it has sufficient heat aging resistance.

[0059] Here, the number of constitutional units derived from non-conjugated polyene (C) per weight average molecular weight (Mw) of the ethylene-α-olefin-non-conjugated polyene copolymer (n C ) or the number of constitutional units derived from non-conjugated polyene (C) (n D ) can be calculated from the molecular weight of the non-conjugated polyene (C) or (D), the weight fraction of the structural units derived from the non-conjugated polyene (C) or (D) in the copolymer (weight fraction (wt%) of (C) or (D)), and the weight average molecular weight (Mw) of the copolymer, according to the following formula: (n C )=(Mw)×{weight fraction of (C) / 100} / molecular weight of non-conjugated polyene (C) (n D )=(Mw)×{weight fraction of (D) / 100} / molecular weight of non-conjugated polyene (D)

[0060] The ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention has a weight average molecular weight (Mw) of 100 to 2000 mol / L, and the number of constituent units (n c ) and (n D ) satisfy the above ranges, the ethylene-α-olefin-non-conjugated polyene copolymer is preferable because it has a low content of long chain branches, excellent curing characteristics when crosslinked using a peroxide, good moldability, and an excellent balance of physical properties such as mechanical properties, and is less likely to cause post-crosslinking and is particularly excellent in heat aging resistance.

[0061] <Production of ethylene-α-olefin-non-conjugated polyene copolymer (S)> The ethylene-α-olefin-non-conjugated polyene copolymer (S) according to the present invention is a copolymer obtained by copolymerizing monomers consisting of ethylene (A), an α-olefin (B) having 3 to 20 carbon atoms, a non-conjugated polyene (C) containing in the molecule a total of two or more partial structures selected from the group consisting of the general formulae (I) and (II), and, if necessary, a non-conjugated polyene (D) containing in the molecule only one partial structure selected from the group consisting of the general formulae (I) and (II).

[0062] The ethylene / α-olefin / non-conjugated polyene copolymer (S) according to the present invention may be prepared by any method as long as it satisfies the above-mentioned requirements (i) to (v). However, it is preferable that the copolymer is obtained by copolymerizing monomers in the presence of a metallocene compound, and it is more preferable that the copolymer is obtained by copolymerizing monomers in the presence of a catalyst system containing a metallocene compound.

[0063] As a specific method for producing the copolymer (A) according to the present invention, for example, the production method using a metallocene catalyst described in JP 2018-119096 A and WO 2015 / 122495 A pamphlet can be adopted.

[0064] <Ethylene-α-olefin copolymer (F)> The ethylene-α-olefin copolymer (F), which is one of the components contained in the copolymer composition for a conveyor belt of the present invention (hereinafter sometimes abbreviated as "component (F)"), is a copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms.

[0065] The α-olefin is preferably an α-olefin having 3 to 12 carbon atoms, more preferably 4 to 8 carbon atoms, in order to obtain a conveyor belt having excellent mechanical strength. Specific examples of such α-olefins include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 9-methyl-1-decene, 11-methyl-1-dodecene, and 12-ethyl-1-tetradecene. Among these, propylene, 1-butene, 1-hexene, and 1-octene are preferably used. These α-olefins may be used alone or in combination of two or more.

[0066] In the component (F) according to the present invention, the content of the structural units derived from ethylene is preferably 50 to 85 mol %, more preferably 50 to 80 mol % (however, the total of the structural units derived from ethylene and the structural units derived from an α-olefin having 3 to 20 carbon atoms is 100 mol %). When the content of the structural units derived from ethylene is within the above range, a copolymer composition for a conveyor belt having excellent compatibility with the component (S) can be obtained.

[0067] The component (F) according to the present invention preferably satisfies the following requirements (i) to (iv). (i) Melting point The melting point of component (F) according to the present invention is preferably 110° C. or lower, more preferably 0 to 105° C., and even more preferably 0 to 100° C. When the melting point of component (F) is within the above range, unmelted component (F) does not remain even at low kneading temperatures, and a conveyor belt that has a small mold shrinkage rate and excellent abrasion resistance can be obtained. The melting point of the component (F) according to the present invention can be measured by the method described in JIS K 7121.

[0068] (ii) Density The density of the component (F) according to the present invention is preferably 840 to 920 kg / m 3 More preferably, it is 850 to 915 kg / m 3and more preferably 860 to 915 kg / m 3 When the density is within the above range, a conveyor belt having a small molding shrinkage rate and excellent strength characteristics and abrasion resistance can be obtained. The density of the component (F) according to the present invention can be measured by the method described in ASTM D1505.

[0069] (iii) MFR The MFR of the component (F) according to the present invention at 190° C. and 2.16 kg is preferably 0.1 to 50 g / 10 min, more preferably 0.2 to 30.0 g / 10 min, and even more preferably 0.3 to 10 g / 10 min. When the MFR is within the above range, a copolymer composition for a conveyor belt having a small mold shrinkage rate and excellent processability can be obtained. The MFR of the component (F) according to the present invention can be measured by the method described in ASTM D1238.

[0070] (iv) Mw / Mn The component (F) according to the present invention preferably has a ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn, as determined by GPC analysis, in the range of 1.5 to 10.0. The component (F) according to the present invention has a weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) of preferably 10,000 to 500,000, more preferably 20,000 to 300,000, and even more preferably 20,000 to 200,000.

[0071] The weight average molecular weight (Mn) of the component (F) according to the present invention, as determined by GPC, is preferably in the range of 1,000 to 250,000, more preferably 2,000 to 150,000, and even more preferably 2,000 to 100,000.

[0072] Furthermore, the component (F) according to the present invention is preferably solid at temperatures from room temperature to about 100°C, and more preferably at temperatures around 90°C. When the weight average molecular weight of the component (F) according to the present invention is within the above range, a conveyor belt having a small molding shrinkage rate and excellent abrasion resistance can be obtained. In addition, since the amount of low molecular weight components is small, the volatilization or protrusion of the low molecular weight components is less likely to occur in the obtained conveyor belt, which is preferable.

[0073] Specifically, the Mw, Mn and Mw / Mn of the component (F) according to the present invention can be measured by a method similar to the method for measuring the molecular weight of the copolymer (S) described in the examples below. The component (F) according to the present invention can be produced by copolymerizing ethylene and an α-olefin by a conventionally known method using, for example, a vanadium catalyst, a Ziegler-Natta catalyst, or a metallocene catalyst. A synthesis method using a metallocene catalyst is preferred from the viewpoint of being able to easily obtain a copolymer satisfying the above physical properties, and specifically, a synthesis method using a catalyst containing a metallocene compound and an aluminum-containing compound as described in International Publication No. 2008 / 152935, or a catalyst consisting of a metallocene compound and an organoaluminum oxy compound or an ionized ionic compound as described in Japanese Patent Application Laid-Open No. 9-40586 is more preferred.

[0074] <Carbon black (G)> Carbon black (G), which is one of the components contained in the copolymer composition for a conveyor belt of the present invention (hereinafter, may be abbreviated as "component (G)"), is a type of known rubber reinforcing agent blended in rubber compositions, and is an inorganic substance generally called carbon black.

[0075] Specific examples of the carbon black (G) used in the present invention include Asahi #55G, Asahi #60G, and Asahi #60UG (all manufactured by Asahi Carbon Co., Ltd.), and Seast (V, SO, 116, 3, 6, 9, SP, TA, etc.) carbon blacks (manufactured by Tokai Carbon Co., Ltd.), and these carbon blacks that have been surface-treated with a silane coupling agent or the like.

[0076] <Anti-aging agent (H)> The antioxidant (H), which is one of the components contained in the copolymer composition for a conveyor belt of the present invention (hereinafter, sometimes abbreviated as "component (H)"), is a conventionally known antioxidant, such as an amine-based antioxidant, a phenol-based antioxidant, or a sulfur-based antioxidant.

[0077] Further, examples of the antiaging agents include aromatic secondary amine-based antiaging agents such as phenylbutylamine and N,N-di-2-naphthyl-p-phenylenediamine; phenol-based antiaging agents such as dibutylhydroxytoluene and tetrakis[methylene(3,5-di-t-butyl-4-hydroxy)hydrocinnamate]methane (trade name: Irganox 1010, manufactured by BASF); thioether-based antiaging agents such as bis[2-methyl-4-(3-n-alkylthiopropionyloxy)-5-t-butylphenyl]sulfide; dithiocarbamate-based antiaging agents such as nickel dibutyldithiocarbamate; 2-mercaptobenzoylimidazole (trade name: Examples of such antioxidants include sulfur-based antioxidants such as Sandant MB (manufactured by Sanshin Chemical Industry Co., Ltd.), 2-mercaptobenzimidazole, zinc salt of 2-mercaptobenzimidazole, dilauryl thiodipropionate, and distearyl thiodipropionate. These antioxidants can be used alone or in combination of two or more.

[0078] <Organic peroxide crosslinking agent (J)> An organic peroxide-based crosslinking agent (J) (hereinafter sometimes abbreviated as "component (J)"), which is one of the components that may be contained in the copolymer composition for a conveyor belt of the present invention, ] is a type of crosslinking agent, and specific examples thereof include dicumyl peroxide (DCP), di-tert-butyl peroxide, 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butylperoxybenzoate, ert-butylperoxyisopropylcarbonate, diacetyl peroxide, lauroyl peroxide, and tert-butylcumyl peroxide.

[0079] Of these, organic peroxide-based crosslinking agents such as dicumyl peroxide (DCP), 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and n-butyl-4,4-bis(tert-butylperoxy)valerate are preferred.

[0080] <Copolymer composition for conveyor belts> The copolymer composition for a conveyor belt of the present invention is a composition containing the ethylene-α-olefin-non-conjugated polyene copolymer (S), the ethylene-α-olefin copolymer (F), the carbon black (G) and the antioxidant (H), and preferably a composition further containing the organic peroxide-based crosslinking agent (J).

[0081] The copolymer composition for a conveyor belt of the present invention contains the above-mentioned components, and therefore has excellent processability, and a conveyor belt obtained from the copolymer composition for a conveyor belt has excellent mechanical properties, heat aging resistance, and abrasion resistance.

[0082] The copolymer composition for a conveyor belt of the present invention preferably contains the above component (S) in an amount of 95 to 5 parts by mass, preferably 90 to 10 parts by mass, and more preferably 80 to 20 parts by mass, and the above component (F) in an amount of 5 to 95 parts by mass, preferably 10 to 90 parts by mass, and more preferably 20 to 80 parts by mass, relative to 100 parts by mass of the total amount of the above components (S) and (F). The copolymer composition for a conveyor belt of the present invention contains the above component (G) in an amount of 5 to 120 parts by mass, more preferably 10 to 100 parts by mass, and the above component (H) in an amount of 0.1 to 20 parts by mass, and more preferably 0.2 to 15 parts by mass, relative to 100 parts by mass of the total amount of the above components (S) and (F). When the copolymer composition for a conveyor belt further contains the above component (J), the component (J) is contained in an amount of 0.1 to 30 parts by mass, and more preferably 0.2 to 25 parts by mass.

[0083] The copolymer composition for a conveyor belt of the present invention may contain, in addition to the above-mentioned components, other compounding agents, such as at least one selected from a crosslinking aid, a softener, an antiaging agent, a processing aid, an activator, a heat stabilizer, a weathering stabilizer, an antistatic agent, a colorant, a lubricant, a thickener, an air bubble inhibitor, a foaming agent, and a foaming aid, depending on the purpose. Each additive may be used alone or in combination of two or more kinds.

[0084] <Crosslinking aid> Examples of the crosslinking aid include sulfur; quinone dioxime-based crosslinking aids such as p-quinone dioxime; acrylic crosslinking aids such as ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate; allyl crosslinking aids such as diallyl phthalate and triallyl isocyanurate; maleimide-based crosslinking aids; divinylbenzene; and metal oxides such as zinc oxide (e.g., ZnO#1·zinc oxide type 2 (JIS standard (K-1410)), manufactured by Hakusui Tech Co., Ltd.), magnesium oxide, and activated zinc oxide (e.g., zinc oxide such as "META-Z102" (trade name, manufactured by Inoue Lime Industry Co., Ltd.)).

[0085] When a crosslinking auxiliary is used, the amount of the crosslinking auxiliary in the copolymer composition for a conveyor belt is usually 0.5 to 10 mol, preferably 0.5 to 7 mol, and more preferably 1 to 6 mol, per mol of the organic peroxide-based crosslinking agent.

[0086] <Softener> Examples of softeners include petroleum-based softeners such as process oil, lubricating oil, paraffin oil, liquid paraffin, petroleum asphalt, and Vaseline; coal tar-based softeners such as coal tar; fatty oil-based softeners such as castor oil, linseed oil, rapeseed oil, soybean oil, and coconut oil; waxes such as beeswax and carnauba wax; naphthenic acid, pine oil, rosin or derivatives thereof; synthetic polymeric substances such as terpene resins, petroleum resins, and coumarone-indene resins; ester-based softeners such as dioctyl phthalate and dioctyl adipate; and others, such as microcrystalline wax, liquid polybutadiene, modified liquid polybutadiene, hydrocarbon-based synthetic lubricating oils, tall oil, and sub(factice). Of these, petroleum-based softeners are preferred, and process oil is particularly preferred.

[0087] When the copolymer composition for a conveyor belt contains a softener, the blending amount of the softener is generally 2 to 100 parts by mass, and preferably 10 to 100 parts by mass, per 100 parts by mass of the total amount of component (S) and component (F).

[0088] <Processing aids> As the processing aid, a wide variety of processing aids that are generally compounded with rubber can be used.Specific examples include ricinoleic acid, stearic acid, palmitic acid, lauric acid, barium stearate, zinc stearate, calcium stearate, zinc laurate, and esters.Of these, stearic acid is preferred.

[0089] When the copolymer composition for a conveyor belt contains a processing aid, it can be appropriately blended in an amount of usually 1 to 3 parts by mass per 100 parts by mass of the total amount of component (S) and component (F). When the blending amount of the processing aid is within the above range, it is preferable since the processability such as kneading processability, extrusion processability, and injection moldability is excellent. The processing aid may be used alone or in combination with two or more kinds.

[0090] <Activator> Examples of the activator include amines such as di-n-butylamine, dicyclohexylamine, and monoethanolamine; activators such as diethylene glycol, polyethylene glycol, lecithin, triaryl methylate, and zinc compounds of aliphatic or aromatic carboxylic acids; zinc peroxide preparations; octadecyltrimethylammonium bromide, synthetic hydrotalcite, and special quaternary ammonium compounds.

[0091] When the copolymer composition for a conveyor belt contains an activator, the amount of the activator is usually 0.2 to 10 parts by mass, and preferably 0.3 to 5 parts by mass, per 100 parts by mass of the total amount of component (S) and component (F).

[0092] <Foaming agent and foaming assistant> The molded article formed by using the copolymer composition for a conveyor belt of the present invention may be a non-foamed article or a foamed article. When the conveyor belt is a foamed article, it is preferable that the copolymer composition for a conveyor belt contains a foaming agent.

[0093] As the foaming agent, any of commercially available foaming agents can be suitably used. Examples of such foaming agents include inorganic foaming agents such as sodium bicarbonate, sodium carbonate, ammonium bicarbonate, ammonium carbonate, and ammonium nitrite; nitroso compounds such as N,N'-dinitrosoterephthalamide and N,N'-dinitrosopentamethylenetetramine; azo compounds such as azodicarbonamide, azobisisobutyronitrile, azocyclohexylnitrile, azodiaminobenzene, and barium azodicarboxylate; sulfonyl hydrazide compounds such as benzenesulfonyl hydrazide, toluenesulfonyl hydrazide, and p,p'-oxybis(benzenesulfonyl hydrazide)diphenylsulfone-3,3'-disulfonyl hydrazide; and azide compounds such as calcium azide, 4,4'-diphenyldisulfonyl azide, and paratoluenemalonyl azide. Among them, azo compounds, sulfonyl hydrazide compounds, and azide compounds are preferably used.

[0094] When the copolymer composition for a conveyor belt contains a foaming agent, the amount of the foaming agent is appropriately selected depending on the performance required for a molded article produced from the copolymer composition, but the foaming agent is usually used in a ratio of 0.5 to 30 parts by mass, preferably 1 to 20 parts by mass, per 100 parts by mass of the total amount of component (S) and component (F).

[0095] If necessary, a foaming assistant may be used together with the foaming agent. The addition of the foaming assistant is effective in adjusting the decomposition temperature of the foaming agent and uniformizing the bubbles. Specific examples of the foaming assistant include organic acids such as salicylic acid, phthalic acid, stearic acid, and oxalic acid, urea, and its derivatives.

[0096] When the copolymer composition for a conveyor belt contains a foaming aid, the foaming aid is usually used in an amount of 1 to 100 parts by mass, preferably 2 to 80 parts by mass, based on 100 parts by mass of the foaming agent.

[0097] <Method of producing copolymer composition for conveyor belt> The copolymer composition for conveyor belts of the present invention is prepared by kneading the above-mentioned components (S), (F), (G), and (H), and, if necessary, a softener, processing aid, crosslinking aid, etc., for 2 to 20 minutes using an internal mixer (internal mixer) such as a Banbury mixer, kneader, or intermix. Next, additives such as a crosslinking agent, a softener, a crosslinking aid, and a vulcanization accelerator are added to the blend obtained using rolls such as an open roll or a kneader, and the vulcanization accelerator and crosslinking aid are added and mixed as necessary, and the mixture is kneaded at a roll temperature of 40 to 80° C. for 5 to 30 minutes, followed by dispensing.

[0098] When the kneading temperature in an internal mixer is low, the component (J) may be kneaded simultaneously with the components (S), (F), (G) and (H).

[0099] <Conveyor belt> The conveyor belt of the present invention is produced by using the copolymer composition for conveyor belts of the present invention, and specific configurations thereof include the following. The conveyor belt is made of canvas as a core material and has an outer periphery covered with a copolymer composition for conveyor belts. A conveyor belt comprising a steel cord embedded as a core material in a copolymer composition for conveyor belts.

[0100] The canvas is made of a woven fabric of synthetic fibers such as nylon, vinylon, polyester, etc., and the number of layers of the canvas, the thickness of the copolymer composition for a conveyor belt, the belt width, etc. are appropriately determined depending on the purpose of use, but the thickness of the copolymer composition for a conveyor belt is usually about 1.5 to 20 mm.

[0101] The core material made of steel cord is made by twisting together multiple wires with a diameter of about 0.2 to 0.4 mm to form a wire rope with a diameter of about 2.0 to 9.5 mm, and arranging about 50 to 230 steel cords in parallel to form the core material. Generally, the total thickness of the conveyor belt is about 10 to 50 mm.

[0102] The conveyor belt of the present invention can be easily produced by interposing the canvas or steel cord serving as the core material between uncrosslinked sheets formed from the copolymer composition for conveyor belts of the present invention, and crosslinking the sheets by heating and pressurizing them in accordance with a conventional method. The crosslinking conditions are usually 120 to 180°C and 10 to 50 kg / cm. 2 The duration is approximately 10 to 90 minutes. EXAMPLES

[0103] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following description, "parts" refers to "parts by mass" unless otherwise specified. The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0104] In the examples and comparative examples, the following copolymers were used. (1) Ethylene-α-olefin-non-conjugated polyene copolymer (S) [Composition of ethylene-α-olefin-non-conjugated polyene copolymer (S)] The molar ratio and mass fraction (mass%) of each structural unit of the ethylene-α-olefin-non-conjugated polyene copolymer (S) are as follows: 13 The measured values ​​were obtained by C-NMR. The measured values ​​were obtained by using an ECX400P nuclear magnetic resonance apparatus (manufactured by JEOL Ltd.) at a measurement temperature of 120°C, a measurement solvent of orthodichlorobenzene / deuterated benzene = 4 / 1, and an accumulation number of 8000 times. 13 The results were obtained by measuring the C-NMR spectrum.

[0105] [Production Example 1] Production of ethylene-α-olefin-non-conjugated polyene copolymer (S) Ethylene-propylene-5-vinyl-2-norbornene (VNB) copolymer (S-1) was produced using a continuous polymerization apparatus as follows.

[0106] A 300-liter polymerization reactor was continuously fed with 58.3 L / hr of dehydrated hexane solvent from line 1, 4.5 mmol / hr of triisobutylaluminum (TiBA), 0.150 mmol / hr of (C6H5)3CB(C6F5)4, and 0.030 mmol / hr of di(p-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride from line 2. At the same time, 6.6 kg / hr of ethylene, 9.3 kg / hr of propylene, 18 L / hr of hydrogen, and 340 g / hr of VNB were continuously fed into the polymerization reactor from separate lines, and copolymerization was carried out under the conditions of a polymerization temperature of 87°C, a total pressure of 1.6 MPaG, and a residence time of 1.0 hour.

[0107] The ethylene-propylene-VNB copolymer solution produced in the polymerization reactor was continuously discharged at a flow rate of 88.0 L / hr, heated to 170°C (pressure increased to 4.1 MPaG), and fed to a phase separator. At this time, ethanol, a polymerization inhibitor, was continuously introduced into the discharge line in an amount of 0.1 mol times the amount of TiBA in the liquid component extracted from the polymerization reactor.

[0108] In the phase separator, the ethylene-propylene-vinyl alcohol copolymer solution was separated into a dense phase (lower layer) containing most of the ethylene-propylene-vinyl alcohol copolymer and a dilute phase (upper layer) containing a small amount of the polymer.

[0109] The separated thick phase was introduced into heat exchanger K at a rate of 85.4 L / hr, and then into a hopper where the solvent was evaporated and separated to obtain an ethylene-propylene-VNB copolymer at a rate of 7.8 kg / hr.

[0110] The molar ratio (ethylene unit / propylene unit) of the obtained copolymer (S-1) was 70 / 30, the content of VNB units was 1.4 mass%, and the intrinsic viscosity [η] measured in decalin at 135° C. was 2.8 dL / g. The molecular weight distribution of the obtained copolymer (S-1) was bimodal, and the chart obtained by GPC measurement showed two or more peaks, and the area of ​​the peak appearing on the side with the smallest molecular weight was 5% of the total peak area.

[0111] Furthermore, a liquid ethylene-propylene copolymer (kinetic viscosity at 100°C: 2000 mm 2 To the mixture, 15 parts by mass of ethylene-propylene-VNB copolymer (S-1) was added and mixed uniformly.

[0112] (2) Ethylene-α-olefin copolymer (F) (2-1) Ethylene-1-butene copolymer (F-1) Density: 864kg / m 3 Melting point: <50°C, MFR: 3.6g / 10min (manufactured by Mitsui Chemicals, product name: Toughmer) TM DF640〕.

[0113] (2-2) Ethylene-1-butene copolymer (F-2) Density: 862kg / m 3 Melting point: <50°C, MFR: 1.2g / 10min (manufactured by Mitsui Chemicals, product name: Toughmer) TM DF610.

[0114] (2-3) Ethylene-propylene copolymer (F-3) (Mitsui EPT0045) Mooney viscosity (ML(1+4)100°C): 40, ethylene content: 51% by weight (manufactured by Mitsui Chemicals, Inc., trade name Mitsui EPT 0045).

[0115] [Physical Properties of Copolymer Composition for Conveyor Belt] [Mooney viscosity (ML(1+4)100℃)] The Mooney viscosity at 100°C (ML(1+4)100°C) was measured at 100°C using a Mooney viscometer (SMV202 model, manufactured by Shimadzu Corporation) in accordance with JIS K6300.

[0116] [Roll processability] Using an 8-inch roll (manufactured by Nippon Roll Co., Ltd.), the surface temperature of the front roll was 50°C, the surface temperature of the rear roll was 50°C, the rotation speed of the front roll was 18 rpm, the rotation speed of the rear roll was 15 rpm, and the roll gaps were 2 mm and 3.5 mm. The compound was wound around the roll and the condition of the sheet was observed.

[0117] Rating 1: The material did not wrap around the roll at all and bagging occurred immediately. Rating 2: The material temporarily wraps around the roll, but soon peels off from the roll surface, causing bagging. Rating 3: The material wraps around the roll and peels off from the bank area frequently, but there is no bagging. Rating 4: The film easily wraps around the roll, and peeling occurs occasionally from the bank area, but no bagging occurs. Rating 5: The film easily winds around the roll, does not peel off from the bank portion, and does not cause bagging.

[0118] <Physical properties of copolymer composition (crosslinked product) for conveyor belts> [Modulus (MPa), Tensile stress at break (MPa), Tensile elongation at break (%)] The sheet was punched out to prepare No. 3 dumbbell test pieces as described in JIS K 6251 (1993). Using these test pieces, tensile tests were carried out according to the method specified in JIS K6251, section 3, at a measurement temperature of 25°C and a tensile speed of 500 mm / min, and the modulus at 100% elongation (M100), the modulus at 200% elongation (M200), the tensile stress at break (TB), and the tensile elongation at break (EB) were measured.

[0119] [Durometer A hardness] According to JIS K 6253, the hardness of the sheet (Type A durometer, HA) was measured using six 2 mm thick crosslinked sheets with smooth surfaces, stacked on top of each other at the flat part to a thickness of approximately 12 mm. However, specimens with foreign matter, air bubbles, or scratches were not used. The dimensions of the measurement surface of the specimen were set so that the tip of the indenter could be measured at a position 12 mm or more away from the end of the specimen.

[0120] [Heat aging resistance] The sheet was subjected to a heat aging test in which the sheet was held at 180°C for 72 hours (hrs) and 168 hours (hrs) in accordance with JIS K 6257. The hardness, tensile stress at break (MPa), and tensile elongation at break (%) of the sheet after the heat aging test were measured in the same manner as in the above [Hardness (Durometer-A)] item and the above [Modulus, tensile stress at break, tensile elongation at break] item.

[0121] AH (Duro-A) was calculated from the difference in hardness before and after the heat aging test, and Ac(TB) and Ac(EB) were calculated from the tensile stress at break (TB) and tensile elongation at break (EB) before and after the heat aging test to determine the rate of change after the test from the values ​​before the heat aging test, respectively.

[0122] [DIN friction test (amount of wear)] In accordance with JIS-K6264-2:2005, three 2 mm thick crosslinked sheets were stacked to prepare a disk-shaped test piece with a diameter of 16.0±0.2 mm and a thickness of 6 mm. The test piece was then subjected to a DIN abrasion test using a drum with a diameter of 150.0±0.2 mm and a length of 500 mm, which was rotated at 40 revolutions per minute under a load of 1 kgf and an abrasion distance of 40.0±0.2 m, to measure the abrasion amount (DIN abrasion amount: unit: mg).

[0123] Example 1 In the first step, 92 parts by mass of the mixture of ethylene-propylene-VNB copolymer (S-1) and liquid ethylene-propylene copolymer obtained in Production Example 1 (amount of (S-1): 80 parts by mass) and 20 parts by mass of ethylene-1-butene copolymer (F-1) were masticated for 1 minute using a BB-4 type Banbury mixer (manufactured by Kobe Steel, Ltd.), and then 5 parts by mass of zinc oxide (ZnO#1, manufactured by Hakusui Tech Co., Ltd.), 65 parts by mass of carbon black (G-1) (Asahi#70, manufactured by Asahi Carbon Co., Ltd.), 23 parts by mass of paraffin-based process oil (Diana Process PW-380, manufactured by Idemitsu Kosan Co., Ltd.), 1 part by mass of a phenol-based antiaging agent (trade name Irganox 1010, manufactured by BASF) as the antiaging agent (H-1), and 1 part by mass of an imidazole-based antiaging agent (trade name 1, manufactured by BASF) as the antiaging agent (H-2) were added thereto. Two parts by mass of Sandant MB (manufactured by Sanshin Chemical Industry Co., Ltd.) and one part by mass of stearic acid were added and kneaded for two minutes at 140° C. Then, the ram was raised and cleaned, and kneading was continued for another minute, and the kneaded product was discharged at about 150° C. to obtain a first-stage compound.

[0124] Next, in the second step, the mixture obtained in the first step was wound around a 6-inch roll (manufactured by Nippon Roll Co., Ltd., front roll surface temperature 50°C, rear roll surface temperature 50°C, front roll rotation speed 16 rpm, rear roll rotation speed 18 rpm), to which 12 parts by mass of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane (manufactured by Kayaku Akzo Co., Ltd., trade name Trigonox 29-40) was added as an organic peroxide-based crosslinking agent (J-1), and the mixture was kneaded for 10 minutes to obtain an uncrosslinked copolymer composition for conveyor belts. The physical properties of this copolymer composition were evaluated.

[0125] The uncrosslinked copolymer composition for conveyor belts was extruded into a sheet, and then pressed at 145°C for 10 minutes using a 100-ton press molding machine to prepare a crosslinked sheet having a thickness of 2 mm. The physical properties of the crosslinked sheet were measured using the extrusion. The results are shown in Table 1.

[0126] Example 2 The same procedure as in Example 1 was repeated, except that the amount of the (S-1) mixture used in Example 1 was 69 parts by mass (amount of (S-1): 60 parts by mass) and the amount of (F-1) was 40 parts by mass. The physical properties of the obtained uncrosslinked copolymer composition for conveyor belts and the crosslinked sheet were measured. The results are shown in Table 1.

[0127] Example 3 The same procedure as in Example 2 was repeated, except that (F-2) was used instead of (F-1) used in Example 2. The physical properties of the uncrosslinked copolymer composition for conveyor belt and the crosslinked sheet obtained were measured. The results are shown in Table 1.

[0128] Example 4 The same procedure as in Example 2 was repeated, except that (F-3) was used instead of (F-1) used in Example 2. The physical properties of the uncrosslinked copolymer composition for conveyor belt and the crosslinked sheet obtained were measured. The results are shown in Table 1.

[0129] Comparative Example 1 The same procedure as in Example 1 was repeated, except that (F-1) used in Example 1 was not used, the amount of the (S-1) mixture used in Example 1 was 115 parts by mass (amount of (S-1): 100 parts by mass), and the amounts of other additives were as shown in Table 1. The physical properties of the obtained uncrosslinked copolymer composition for conveyor belts and crosslinked sheet were measured. The results are shown in Table 1.

[0130] [Table 1]

Claims

1. A copolymer composition for a conveyor belt, comprising the following components (S), (F), (G) and (H): (S) An ethylene / α-olefin / non-conjugated polyene copolymer having structural units derived from ethylene (A), an α-olefin (B) having 3 to 20 carbon atoms, and a non-conjugated polyene (C) containing in the molecule two or more partial structures in total selected from the group consisting of the following general formulas (I) and (II), and satisfying the following requirements (i) to (v); (F) an ethylene / α-olefin copolymer containing structural units derived from ethylene and structural units derived from an α-olefin having 3 to 20 carbon atoms (with the proviso that the total of the structural units derived from ethylene and the structural units derived from an α-olefin having 3 to 20 carbon atoms is 100 mol %), wherein the α-olefin is 1-butene; (G) carbon black; (H) anti-aging agent; Ethylene / α-olefin / non-conjugated polyene copolymer (S); 【Chemistry 1】 (i) The molar ratio of ethylene to α-olefin is from 40 / 60 to 99.9 / 0.

1. (ii) The weight fraction of the constituent units derived from the non-conjugated polyene (C) is 0.07% by weight to 10% by weight in 100% by weight of the ethylene / α-olefin / non-conjugated polyene copolymer. (iii) The weight average molecular weight (Mw) of the ethylene-α-olefin-non-conjugated polyene copolymer, the weight fraction of the constituent unit derived from the non-conjugated polyene (C) (weight fraction (wt %) of (C)), and the molecular weight of the non-conjugated polyene (C) (molecular weight of (C)) satisfy the following formula (1): 4.5≦Mw×weight fraction of (C) / 100 / molecular weight of (C)≦40...Equation (1) (iv) Complex viscosity η* at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurement (190 ° C) using a rheometer ( ω =0.1) (Pa sec) and complex viscosity η* at frequency ω = 100 rad / s ( ω =100) (Pa sec) P(η* ( ω =0.1) / η* ( ω =100) ), the intrinsic viscosity [η], and the weight fraction of the constitutional unit derived from the non-conjugated polyene (C) (weight fraction of (C)) satisfy the following formula (2). P / ([η] 2.9 ) ≦ weight fraction of (C) × 6 ... formula (2) (v) Long Chain Branches (LCB) per 1000 carbon atoms obtained using 3D-GPC 1000C ) and the natural logarithm of the weight average molecular weight (Mw) [Ln(Mw)] satisfy the following formula (3). LCB 1000C ≦1-0.07×Ln(Mw)・・・Formula (3)

2. The copolymer composition for a conveyor belt according to claim 1, further comprising the following (J): (J) an organic peroxide-based crosslinking agent;

3. The copolymer composition for a conveyor belt according to claim 1 or 2, wherein the ethylene-α-olefin-non-conjugated polyene copolymer (S) has an intrinsic viscosity [η] of 0.1 to 5 dL / g and a weight average molecular weight (Mw) of 10,000 to 600,000.

4. The copolymer composition for a conveyor belt according to any one of claims 1 to 3, wherein the non-conjugated polyene (C) constituting the ethylene-α-olefin-non-conjugated polyene copolymer (S) is 5-vinyl-2-norbornene (VNB).

5. The copolymer composition for a conveyor belt according to any one of claims 1 to 4, wherein the ethylene / α-olefin / non-conjugated polyene copolymer (S) further contains a constitutional unit derived from a non-conjugated polyene (D) containing only one partial structure selected from the group consisting of the formulae (I) and (II) in the molecule, in a weight fraction of 0 to 20% by weight (wherein the total of the weight fractions of (A), (B), (C), and (D) is taken as 100% by weight), and satisfies the following requirement (vi); (vi) the weight average molecular weight (Mw) of the ethylene-α-olefin-non-conjugated polyene copolymer, the weight fraction of the structural unit derived from the non-conjugated polyene (C) (weight fraction (wt%) of (C)), the weight fraction of the structural unit derived from the conjugated polyene (D) (weight fraction (wt%) of (D)), the molecular weight of the non-conjugated polyene (C) (molecular weight of (C)), and the molecular weight of the conjugated polyene (D) (molecular weight of (D)) satisfy the following formula (4): 4.5≦Mw×{(weight fraction of (C) / 100 / molecular weight of (C))+(weight fraction of (D) / 100 / molecular weight of (D))}≦45...Equation (4)

6. The copolymer composition for a conveyor belt according to any one of claims 1 to 5, wherein the non-conjugated polyene (D) constituting the ethylene-α-olefin-non-conjugated polyene copolymer (S) is 5-ethylidene-2-norbornene (ENB).

7. A conveyor belt comprising the copolymer composition for conveyor belts according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Heat-resisting belt

    JP1999246017A

  • Crosslinkable rubber composition and its application

    JP2003128847A

  • Ethylene / α-olefin / non-conjugated polyene copolymer composition

    JP2019155693A

  • Ethylene copolymer composition and hose product

    JP2020084136A

  • ETHYLENE / α-OLEFIN / NON-CONJUGATED POLYENE COPOLYMER, PRODUCTION METHOD THEREFOR, AND USE THEREFOR

    WO2015122495A1